PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN AGRIBISNIS TANAMAN SAYURAN PESERTA DIDIK KELAS XI AGRIBISNIS TANAMAN PANGAN DAN HORTIKULTURA SMK NEGERI 4 GOWA - Nurlinda Nurlinda; Patang Patang; Lahming Lahming (Jurnal Pendidikan Teknologi Pertanian, 2018)
This research is a classroom action research that aims to know the improvement of learn outcomes on  vegetables agribusiness subjects by using cooperative learning model of jigsaw type of class XI  state vocational school 4 Gowa. The subjects of this study were the learners of class XI ATPH 3 state vocational school 4 Gowa school year 2017/2018 with amount of 21 learners undertaken in two cycles and each cycle is held four times meetings. Data collection techniques used are through the initial tests and tests at the end of the cycle. The results of this study indicate that the implementation of jigsaw type cooperative learning model at the subjects of agribusiness of vegetable crops in the learners of class XI ATPH 3 state vocational school 4 Gowa can improve the learning outcomes. This is shown from the results of research cycle I with an average value of 69.85%, while for classical exhaustiveness reached 42.86% and on the implementation of cycle II increased with an average value of 81.90%, while for classical exhaustiveness reached 95, 23%.